Sustentabilidade nas contratações públicas em uma Universidade Federal do Nordeste: um estudo de caso - Assumpção, Cleverton Torres (2019)
The perception that the Public Administration is similar to a large consumer and aggressor of the environment leads the government system to establish public policies that reject unsustainable consumption patterns and promote social and environmental behavior for sustainable national development. In this scenario, the present study aims to propose a plan of action to improve the process of sustainable public procurement in a Federal University in the Northeast. The research has an applied nature with proposition of a plan of action; is descriptive of the objectives, but also takes the form of exploratory research, since the theme chosen is contemporary and not yet researched within the Institution. The approach is mixed, with qualitative and quantitative aspects, whose data were treated and consolidated with the use of percentage calculations in tables and graphs, establishing the degree of importance of the information collected. As for the procedures, the research is a bibliographical, documentary and case study, collecting data from the electronic precincts executed at the Federal University of Alagoas (UFAL), through the Comprasnet site, from 2015 to 2018, focusing on the acquisition of goods and contracting of sustainable services, compared with the information contained in the platform of the Purchasing Panel of the Federal Government. The research involved the collection of relevant legislation, institutional documents to obtain a flowchart of the procurement process with the actors involved and with this, to subsidize the action plan. The analysis of the documents shows that the University does not have a PGLS and the sustainable biddings are carried out independently by the internal and external control bodies. The information collected from the bidding processes shows that sustainable procurement and procurement are larger than those shown in the Procurement Panel, due to the failure to insert the CATMAT code of products registered as sustainable in the internal phase of the bidding process. The participation of regional or local ME / EPP based in the State of Alagoas in electronic trading is insipient, requiring the Institution to promote an internal policy to Foster the participation of these business segments.